Maintaining balance for Christian counsellors when their work is a calling : a thesis presented in partial fulfilment of the requirement of the Master of Arts in Psychology at Massey University, Albany, New Zealand - Frost, Leanne (Massey University, 2021)
The purpose of the study was to examine the daily lives of Christian Counsellors with a calling, with a view to understanding how they manage their work-non work boundaries. Calling is defined as perceiving a summons from an external source to any work that provides meaning and purpose, and which contributes to the greater good (Duffy, Dik, Douglass, England, & Velez, 2018). For Christian Counsellors maintaining balance is important as mental health demands increase and telehealth and working from home options become more utilised. Having a calling offers satisfaction, meaning and purpose, however it can also lead to overwork. This study was based on the framework of the Job Demands-Resources and Boundary Management Theory. Using a qualitative approach with seven experienced counsellors in Auckland, New Zealand, results showed for Christian counsellors calling can be both a demand and a resource. Demands were identified as a responsibility and duty to represent God to clients and to use relational gifts in the service of others which could lead to over-giving. A further demand was a desire to reveal God to clients constrained by Counselling Codes of Ethics. Resources were identified as a feeling of privilege and identity that was enriched by the call. Resources of being gifted relationally, with faith as a supportive strategy were identified. Boundary Theory identified participants have flexible permeable boundary styles and highly matching role personas making the need for deliberate boundaries important. Conversations revealed maintaining balance is supported by being deliberate, giving oneself permission with strategies for maintaining balance being learned across time.
Keywords: 520303 Counselling psychology